2015
DOI: 10.1080/15524256.2015.1107806
|View full text |Cite
|
Sign up to set email alerts
|

Adult Hospice Social Work Intervention Outcomes in the United States

Abstract: A descriptive and critical analysis of the available empirical literature on social work psychosocial intervention outcomes for adult hospice patients and caregivers was conducted. The electronic bibliographic databases CINHAL (EBSCO), MEDLINE, ProQuest, EMBASE, Campbell Collaboration, and The Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library) were searched. Search criteria were (a) social work interventions, (b) intervention was tested, (c) adult hospice patients and/or caregivers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…57,81 Domain 4: Social Aspects of Care Table 4). 106,110 There is low-quality evidence that social work interventions lead to the identification of and access to social services. One review found that various caregiver support services helped to identify caregivers' direct support service needs, decreased caregiver role overload, and led to a nonsignificant increase in social support and benefits finding; however, the review reported no effect estimate across studies.…”
Section: (Im In)mentioning
confidence: 99%
See 1 more Smart Citation
“…57,81 Domain 4: Social Aspects of Care Table 4). 106,110 There is low-quality evidence that social work interventions lead to the identification of and access to social services. One review found that various caregiver support services helped to identify caregivers' direct support service needs, decreased caregiver role overload, and led to a nonsignificant increase in social support and benefits finding; however, the review reported no effect estimate across studies.…”
Section: (Im In)mentioning
confidence: 99%
“…One review found that various caregiver support services helped to identify caregivers' direct support service needs, decreased caregiver role overload, and led to a nonsignificant increase in social support and benefits finding; however, the review reported no effect estimate across studies. 110 There is very low-quality evidence that social support interventions do not impact social support outcomes. A review reported findings from a single RCT of group therapy for patients with life-limiting illness that showed no demonstrable difference in social support; the review did not report effect estimates.…”
Section: (Im In)mentioning
confidence: 99%
“…A clear role description of social work in palliative care – operationalised by a well-defined set of core competencies – is another prerequisite. 88 The previous paragraph already mentioned the importance of social workers clearly articulating their role. Yet, the dominant focus on physical aspects in palliative care often jeopardises the role articulation of social workers.…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes measurement has documented significant client improvement, demonstrating the impact of social work services on patient outcomes in hospices and hospitals. 3,12,13 Attention to specific psychosocial domains has resulted in reduced problems in the associated domain. 14,15 The use of an electronic medical record (EMR) in hospice resulted in greater attention to the domains included in assessment tools.…”
Section: Literature Reviewmentioning
confidence: 99%